Determining the Role of Benzyl Adenine in Advancing Goals of Biotechnology - Firoozeh Chamandoosti (Innovations in Microbiology and Biotechnology Vol. 3, 2022)
Today, no one can deny the importance of plant pests and diseases, as well as their destructive role in human life. It is obvious that improving plant productivity for various purposes of plant protection against plant diseases is the best and safest method for plant protection. Due to the limitations of conventional plant breeding, we must resort to alternative methods. Biotechnology is a modern and powerful tool for improving plant and food production. Gene transfer and tissue culture are two critical components of biotechnology. The development of regeneration systems for cells and plants transformed by gene transfer should be inexpensive and simple. Benzyl adenine (BA) is a plant hormone that is inexpensive and easy to obtain, as we observed and investigated in the case of several different plant species.